Tracing the nitrogen metabolites of glycine using 15N‐glycine and mass spectrometry. (15th April 2015) - Liu, Lin‐na; Fu, Ting‐ting; Xu, Xun‐fu; Fu, Chuan; Fang, Mei‐juan; Liu, Yan; Xu, Peng‐xiang; Zhao, Yu‐fen
<x xml:space="preserve">Abstract</x> Rationale Glycine is the smallest amino acid used in protein synthesis, but it is also a very important precursor for the biosynthesis of other nitrogen‐containing metabolites, such as purine nucleosides and nucleotides for synthesis of RNA, DNA etc. Abnormalities in glycine metabolism therefore cause diseases such as cancer. A quick and unambiguous method to trace the metabolites arising from glycine is required for targeting defect points within metabolic networks. Methods This paper describes a method for using 15N‐glycine to culture A549 cancer cells for use with high‐resolution mass spectrometry (HRMS) and tandem mass spectrometry (HRMS2) that can detect the (M+1)/M pair peaks appearing in the cell metabolites. The 1 Da difference in the pair peaks can be used to point out and identify the nitrogen metabolites of glycine. Results Thirteen nitrogen‐containing metabolites derived from glycine were confirmed. Among them were metabolites containing purine, such as adenine, adenosine, AMP, ADP, ATP, S‐adenosylmethionine and γ‐glutathione; these were the most sensitive to the 15N‐glycine‐enrichment technique. Therefore, they are promising biomarkers for monitoring the glycine metabolism network. Conclusions The method developed here could be applied to investigations of metabolism of other amino acids, and for drug discovery studies targeting the enzymes related to amino acid metabolism. Copyright © 2015 John Wiley & Sons, Ltd.